Why Milton matters : a new preface to his writings - Wittreich, Joseph Anthony (Palgrave Macmillan, 2006)
A poet of the seventeenth century, Milton with his future gaze may prove to be (singularly among the triumvirate of Chaucer, Shakespeare, and Milton) the poet for the new millennium--the poet for the twenty-first century. Milton will be so to the extent that through him we see the upheavals in the humanities as deriving not from a revision of the canon but rather, as Bill Readings insists in The University in Ruins, from?a crisis in the function of the canon? and, then, to the extent that Milton shocks us into the recognition that poets sometimes deliver messages at odds with those with which they are credited.